(untitled) (Community Based Medical Journal, 2025)
The movements of the shoulder joint are influenced by the angles of the scapula. Among all the angles of the scapula, the gleno-polar angle measures the obliquity of the glenoid articular surface in relation to the scapular body, which is important for deciding the treatment and prognosis of floating shoulder. Therefore, a detail knowledge of scapular angles helps us to understand and treat the different shoulder disorders. We proposed this study to observe the angles of the left scapula in a Bangladeshi population through radiographic analysis. This cross-sectional, analytical study was conducted among 100 adult Bangladeshi people (50 male and 50 female) in the Department of Anatomy, Dhaka Medical College, Bangladesh, from July 2017 to June 2018. Radiographs of anterior-posterior view of the left shoulder was taken in the Department of Radiology & Imaging of the same institution. The procedure was done by using measurement toolbox of DICOM (Digital Imaging & Communications in Medicine) software with angle option. The superior, inferior, lateral and gleno-polar angles were found greater in male comparing to its female counterpart. There is no previous radiological study done on the angles of the scapula in Bangladesh by using such radiological software. This method is a non-invasive one. Measurement of angles of scapula by radiographic analysis provides accurate information about the pathomechanics of shoulder joint movement. CBMJ 2025 July: vol. 14 no. 02 P:15-20